Coping Strategies in Patients with Schizophrenia at Naimata Mental Hospital - Haman, Generosus Magnum Marianus; Regaletha, Tadeus A.L; Dodo, Dominirsep O (Faculty of Public Health, Nusa Cendana University, 2020)
Schizophrenia is one of the most common medical diagnoses of mental disorders and is a severe mental disorder that is influenced by biological, psychological and environmental factors. Schizophrenics have cognitive and behavioral disorders, so they have difficulty in determining appropriate coping. Koping is meant a process in order to change the cognitive domain and or behavior constantly to regulate and control external and internal demands and pressures. The purpose of this study was to determine coping strategies in schizophrenia the maintenance stage patients in the inpatient ward of the Naimata Kupang mental hospital. This type of research is descriptive research with a quantitative approach. The population in this study were 70 patients with Schizophrenia. The sample in this study were 30 patients with schisophrenia. The results obtained are that there is no impact from physical health and education on the application of coping strategies to Schizophrenia patients. The impact of positive beliefs (Emotion Focused Coping), problem solving skills (Problem Focused Coping), social and occupational support or socioeconomic status on the application of coping strategies to schizophrenia patients. The type of Emotion Focused Coping used is the highest type of Distancing and the Escape-Avodiance type while for the type of use of Problem Focused Coping there are Confrontative-Coping, Planfull Problem Solving and Seeking Social Support. Hospitals and families are expected to always provide support to patients both in the form of verbal and non verbal, material, and motivational support to be able to support the healing process of schizophrenic patients.